Hubungan antara Transfer Pricing dan Sales Growth dengan Tax Avoidance (Studi Empiris pada Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2023) - Pangestika, Imelda; Wahyudi, Ilham; Ridwan, Muhammad (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the Relationship between Transfer Pricing and Sales Growth with Tax Avoidance in Energy Companies Listed on the Indonesia Stock Exchange for the period 2019-2023. The population in this study was 66 companies and a sample of 54 companies with a period of 5 years. The sampling technique used was purposive sampling. The data used are secondary data and the method used is panel data regression analysis with the help of the Eviews 9 program to obtain a comprehensive picture of the relationship between one variable and another. The results of this study are that the Transfer Pricing variable has no effect on Tax Avoidance, while the Sales Growth variable has an effect on Tax Avoidance. The results of the simultaneous regression analysis showed that Transfer Pricing and Sales Growth together affect Tax Avoidance.
Keywords: Transfer Pricing; Sales Growth; Tax Avoidance